2016
DOI: 10.7155/jgaa.00392
|View full text |Cite
|
Sign up to set email alerts
|

A navigation system for tree space

Abstract: The reconstruction of evolutionary trees from data sets on overlapping sets of species is a central problem in phylogenetics. Provided that the tree reconstructed for each subset of species is rooted and that these trees fit together consistently, the space of all parent trees that 'display' these trees was recently shown to satisfy the following strong property: there exists a path from any one parent tree to any other parent tree by a sequence of local rearrangements (nearest neighbour interchanges) so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For instance, it may help studying how trees from the same stand and also between different stands are connected via common topological rearrangements (e.g. Nearest Neighbour Interchange, see also ( 32 )), which has a great potential for development of better tree search strategies in the presence of missing data. Note, that for supertree methods distinct trees can have identical score even without missing data ( 5, 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it may help studying how trees from the same stand and also between different stands are connected via common topological rearrangements (e.g. Nearest Neighbour Interchange, see also ( 32 )), which has a great potential for development of better tree search strategies in the presence of missing data. Note, that for supertree methods distinct trees can have identical score even without missing data ( 5, 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it allows investigating scoring landscapes imposed by missing data as well as studying how trees from the same stand and also between different stands are connected via common topological rearrangements (e.g. Nearest Neighbour Interchange, see also 30 ). This knowledge has a great potential for development of better tree search strategies in the presence of missing data 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Bordewich [Bor03, Proposition 2.9] and Mark et al [MMS16] showed that the space of rooted phylogenetic trees that display a set of triplets (trees on three leaves) is connected under NNI. Furthermore, Bordewich et al [BLS17] showed that the space of rooted phylogenetic networks that display a set of rooted phylogenetic trees is connected.…”
Section: Network Displaying Networkmentioning
confidence: 99%
“…According to [1], let T ∈ RB(X) and let e = (v, u) be an arc of T. We say that T 1 ∈ RB(X) is an rSPR-neighbour of T if T 1 can be obtained from T by the following procedure. Let t u be the subtree of T rooted at u. Delete arc e, pruning the subtree t u .…”
Section: Rooted Subtree Pruned and Regraft (Rspr)mentioning
confidence: 99%